Ammonium alleviates iron deficiency of drip-irrigated rice seedlings in low soil temperature in calcareous soil. (4th July 2019) - Zhang, Xinjiang; Liu, Hui; Meng, Chaoran; Zhang, Zhiyang; Wang, Mengmeng; Wei, Changzhou
ABSTRACT: Paddy rice ( Oryza sativa L.) is easy to suffer from iron (Fe) deficiency in drip-irrigated (DI) calcareous soils, especially at the seedling stage. Low soil temperature and the soil nitrogen (N) is dominated by nitrate (NO 3 − ) is probably the reason of Fe chlorosis in this stage. The objective of this experiment was to elucidate the causes of Fe deficiency induced by low soil temperature and the mechanism of ammonium (NH 4 + ) alleviate Fe deficiency of DI rice. Applying different N forms (NH 4 + orNO 3 − ) to two rice cultivars (cv. 'T43' and 'T04', Fe-efficient and Fe-inefficient genotype, respectively) under different soil temperatures to study the growth and Fe uptake of DI rice. The results showed that low soil temperature reduced the root biomass and root activity of rice significantly, which in turn, resulted in low leaf SPAD value and Fe uptake of rice. The rice fed withNH 4 + had improved root activity and bigger root surface area, higher rhizosphere soil DTPA-Fe concentration and more Fe uptake than fed withNO 3 − under low soil temperature. The results indicatedNH 4 + alleviates Fe deficiency of DI rice by improving the availability of rhizosphere soil Fe, increasing the root surface area and root activity. Application ofNH 4 + − N to DI rice is a promise agronomic measure to alleviate Fe deficiency.